Designing for practice: understanding technology use in rural community-based youth mental health contexts. Issue 2 (3rd April 2019) - Orlowski, Simone; Matthews, Ben; Lawn, Sharon; Jones, Gabrielle; Bidargaddi, Niranjan; Venning, Anthony
Abstract: Social and mobile technologies appear to have remarkable scope to improve the access and quality of remote frontline mental health services. However, their potential has not yet been realised, due in part to an insufficient appreciation of remote mental health care settings as contexts for design. This study reports on a participatory design (PD) process involving mental health practitioners and clients, focusing on three participatory future workshops. Visioning, Scenario building and Mock-up phases encouraged participants to explore: (1.) What is needed and possible? (2.) Where would it fit? Who would use it and why? and (3.) How would it look, feel & function? These activities generated a contextualised understanding of frontline mental health service provision, and the possible roles of technology within it. PD methods were effective in a number of respects: defining domain criteria associated with mental health care; supporting community-based youth mental health professionals to articulate the roles of technology in their work; and identifying new opportunities for technologies in this space. Mental health applications can do more than provide a means of self-tracking or serve as a treatment surrogate; rather they can support clients' autonomy with respect to self-discovery and direction-setting in treatment and recovery.